AGO recommendations for the diagnosis and treatment of patients with locally advanced and metastatic breast cancer: update 2019 - Thill, Marc; Jackisch, Christian; Janni, Wolfgang; Müller, Volkmar; Albert, Ute-Susann; Bauerfeind, Ingo; Blohmer, Jens; Budach, Wilfried; Dall, Peter; Diel, Ingo; Fasching, Peter A.; Fehm, Tanja; et al. (Breast care, 2019)
Every year the Breast Committee of the Arbeitsgemeinschaft Gynäkologische Onkologie (German Gynecological Oncology Group, AGO), a group of gynecological oncologists specialized in breast cancer and interdisciplinary members specialized in pathology, radiologic diagnostics, medical oncology, and radiation oncology, prepares and updates evidence-based recommendations for the diagnosis and treatment of patients with early and metastatic breast cancer. Every update is performed according to a documented rule-fixed algorithm, by thoroughly reviewing and scoring the recent publications for their scientific validity and clinical relevance. This current publication presents the 2019 update on the recommendations for metastatic breast cancer.